How economists model the world into numbers - Boumans, Marcel (London ; New York : Routledge, 2005)
This book provides a critical analysis of the economist's favourite tool, and as such will be an enlightening read for some, and an intriguing one for others.
Book Cover; Title; Copyright; Contents; 1 Introduction; 2 A new practice; 3 Autonomy; 4 Design of experiments; 5 Measurement; 6 Rigour; 7 Conclusions; Notes; Bibliography; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Economics, Mathematical; Economics -- Mathematical models; Econometrics; Economics -- Methodology -- History -- 20th century; Economics, Mathematical -- History -- 20th century; Économie politique -- Modèles mathématiques.; Économétrie.; Économie politique -- Méthodologie -- Histoire -- 20e siècle.; Mathématiques économiques.; Mathématiques économiques -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Econometrics; BUSINESS & ECONOMICS -- Statistics; Econometrics; Economics, Mathematical; Economics -- Mathematical models; Economics -- Methodology; 1900-1999; History